Subcritical Water Process for Reducing Sugar Production from Biomass: Optimization and Kinetics - Maktum Muharja; Arief Widjaja; Rizki Fitria Darmayanti; Nur Fadhilah; Bramantyo Airlangga; Abdul Halim; Siska Nuri Fadilah; I Made Arimbawa (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2022)
The competitive reactions of lignocellulose hydrolysis and monosaccharide degradation in the subcritical water (SCW) hydrolysis of coconut husk were investigated to optimize the reducing sugar yield. Optimization analysis was performed by response surface methodology (RSM) and kinetics studies. Parameters of process optimization were varied at 130-170 °C for 15-45 min. The reducing sugars were measured using the Dinitro salicylic acid method. The sugar yield increased when the temperature increased from 130 °C to 170 °C. The highest reduction sugar yield of 4.946 g/L was obtained at 183.6 °C for 4.8 min and 23.4 liquid/solid ratio (LSR). Kinetics studies were carried out at temperature variations of 150, 170, and 190 °C and pressures of 60, 80, and 100 bar for 5 to 60 min. The yield of reducing sugar decreased with increasing temperature. The kinetic model 2B is the best method to explain the competitive reaction kinetics of coconut husk hydrolysis. This research is an innovation to increase the reducing sugar to make the process more commercially viable. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).